Leaching Behaviour of Nitrogen in Forage Rice Cultivation that Applied with Animal Manure - . Gusmini; Kazuyuki Nishimura; . Adrinal; Tomio Itani (UNIVERSITY OF LAMPUNG, 2013)
Increased use of N fertilizer may substantially increase of nitrate nitrogen (NO3-N) leaching, which potentially pollutes groundwater. Leaching behaviour of nitrogen (N) was observed in the paddy field of forage rice cultivation. Two kinds of animal manure, cattle manure (CM) and poultry manure (PM) at 5 levels of N application (0, 70, 140, 210, 280 kg N ha-1) as the organic N sources, and without any chemical fertilizers. “Tachisuzuka” forage rice variety was conducted in the experimental plot. Porous ceramic cups were installed in triplicate of each treatment at 45 cm depth to collect the percolation water samples during the cultivation rice periods. The concentration of total N, NH4-N, NO2-N and NO3-N of water (surface and percolation) and soil sample solution were analysed using a Hach DR/2800 spectrophotometer. Result showed that NO3-N leaching was higher than NH4-N in the percolation water during the cultivation of forage rice periods. The highest NO3-N leaching was found in 280 kg N ha-1 (6.3 mg L-1), that it was indicated on the polluted levels. The highest of biomass production was in N280 (16.22 t ha-1) and nearly similar result in N140, N210 and N280. It was concluded that the best application of N-fertilizer in 140 kg N ha-1 because it greatly enhanced N-fertilizer efficiency, and decreased steadily of NO3-N concentration leaching in the environment of the groundwater.Keywords: Ammonium (NH4-N), Forage rice, N behavior, Nitrate (NO3-N), N leaching[How to Cite: Gusmini, K Nishimura, Adrinal, and T Itani. 2013. Leaching Behaviour of Nitrogen in Forage Rice Cultivation that Applied with Animal Manure. JTrop Soils 18 (3): 209-216. Doi: 10.5400/jts.2013.18.3.209][Permalink/DOI: www.dx.doi.org/10.5400/jts.2013.18.3.209]REFERENCESAgrawal GD, SK Lunkad and T Malkhed. 1999. Difusse agricultural nitrate pollution of groundwater in India. Water Sci Technol 20: 67-75.Asada K, T Nishimura, C Kato, K Toyota and M Hosomi. 2013. Phyto-purification of livestock-derived organic waste by forage rice under subtropical climate. Paddy Water Environ 11: 559-571.Kamiji Y and T Sakuratani. 2011. Analysis of Optimum Spikelet Number and Plant N in Rice at Tanazawa Paddy Field. J Agric Sci 56: 93-102.Kato H. 2008. Development of rice varieties for whole crop silage (WCS) in Japan. JARQ 42: 231-236.Keeney DR. 1982. Nitrogen management for maximum efficiency and minimum pollution. In: Stevenson FJ (ed). Nitrogen in Agricultural Soils. Agron. Monogr. 22. ASA, CSSA, and SSSA, Madison. Wisc, pp 605-649.Kumazawa K. 2002. Nitrogen fertilization and nitrate pollution in groundwater in Japan: Present status and measures for sustainable agriculture. Nutr Cyc Agroecocyst 63: 129-137.Kyaw KM, K Toyota, M Okazaki, T Motobayashi and H Tanaka. 2005. Nitrogen balance in a paddy field planted with whole crop rice (Oryza sative cv. Kusahonami) during two rice-growing seasons. Biol Fertil Soils 42: 72-82.Liu GD, WL Wu and S Zhang. 2005. Regional differentiation of non-point source pollution of agriculture-derived nitrate nitrogen in groundwater in northern China. Agric Ecosys Environ. 107: 211-220.Matsushita K, S Iida, O Ideta, Y Sunohara, H Maeda, Y Tamura, S Kouno and M Takakuwa. 2011. “Tachisuzuka”, a new rice cultivar with high straw yield and high sugar content for whole-crop silage use. Breeding Sci 61: 86-92.Ministry of Agriculture, Forestry and Fisheries (MAFF). 2013. Recent situation and research of rice for whole crop silage in Japan. Accessed 18 August 2013.Ookawa T, K Yasuda, H Kato, M Sakai, M Seto, K Sunaga, Motobayashi, S Tojo and T Hirasawa. 2010. Biomass production and lodging resistance in ‘Leaf Star’, a new long-culm rice forage cultivar. Plant Prod Sci 13: 58-66.Okajima H and H Imai. 1973. Nutrient supplying power of soils. II. Contribution of mass flow to the nutrient supply in flooded rice fields. Jpn J Soil Sci Plant Nutr 44: 296-300. Sahu SK and PK Samant. 2006. Nitrogen loss from rice soil in Orissa. Orissa Review. India. Sakai M, S Iida, H Maeda, Y Sunohara, H Nemoto and T Imbe. 2003. New rice varieties for WCS use in Japan. Breed Sci 53: 271-275.Sakai M, M Okamoto, K Tamura, R Kaji, R Mizobuchi, H Hirabayashi, T Yagi, M Nishimura and S Fukaura. 2008. “Tachiaoba”, high yielding rice variety for whole crop silage. Breed Sci 58: 83-88.Suprapti H, M Mawardi and D Shiddieq. 2010. Nitrogen transport and distribution on paddy rice soil under water efficient irrigation method. Paper Presented on International Seminar of ICID, Yogyakarta. Indonesia. Toriyama K and H Ishida. 1987. Method of estimating time of NH4-N disappearance in paddy field by soil solution analysis. Jpn J Soil Sci Plant Nutr 58: 747-749.Wang MY, MY Siddiqi, TY Ruth and ADM Glass. 1993. Ammonium uptake by rice roots. II. Kinetic of 13NH4+ influx across the plasmalemma. Plant Physiol 103: 1259-1267.Wang JY, SJ Wang and Y Chen. 1995. Leaching loss of nitrogen in double-rice-cropped paddy fields in China. Acta Agricul Zhejiangensis 7: 155-160.Zhu JG, Y Han, G Liu, YL Zhang and XH Shao. 2000. Nitrogen in percolation water in paddy fields with a rice/wheat rotation. Nutr Cycl Agroecosyst 57: 75-82.Zhuo S and M Hosomi. 2008. Nitrogen transformations and balance in a constructed wetland for nutrient polluted river water treatment using forage rice in Japan. Ecol Eng 32: 147-155.Zhuo S, H Iino, S Riya, M Nishikawa, Y Watanabe and M Hosomi. 2011. Nitrogen transformations in paddy field applied with high load liquid cattle waste. J Chem Engin Jpn 44: 713-719.